Effect of Tin Oxide/Black Paint Coating on Absorber Plate Temperature for Improved Solar Still Production: A Controlled Indoor and Outdoor Investigation. (22nd January 2022) - Rasachak, Sayfar; Khan, Rana Sami Ullah; Kumar, Laveet; Zahid, Taiba; Ghafoor, Usman; Selvaraj, Jeyraj; Nasrin, Rehena; Ahmad, Muhammad Shakeel
Abstract : The ever-increasing water stress and availability of fresh drinking water are becoming a major challenge in rural and urban communities. The current high-end and large-scale technologies are becoming way more expensive and not friendly to the environment. In this regard, solar still is becoming a prominent and promising future technology due to its environment-friendly nature, less maintenance and operational costs, and simple design. The technological challenge regarding solar still is its low distillate yield. In this study, an attempt has been made to investigate the effect of tin oxide (SnO2 ) on the absorption surface of solar still towards improvement in sunlight absorption, which would lead to high distillate production rates. Various concentrations of SnO2, i.e., 0.5wt%, 1 wt%, 3 wt%, 5 wt%, 7 wt%, 10 wt%, 15 wt%, and 20 wt%, have been mixed in black and applied on the absorber plate to further optimize the suitable concentration. The experiments have been performed in both indoor (simulated) and outdoor conditions. An increase in surface temperature of absorber plate has been observed with increasing concentration of SnO2 under both the indoor and outdoor conditions, which is due to high solar spectrum absorption properties of SnO2 in the ultraviolet (UV) and near to far-infrared (IR) regions. The highest surface temperature of 101.61°C has been observed for specimens containing 15 wt% SnO2 in black paint under indoor conditions at 1000W/m 2 irradiation levels, which is 53.67% higher compared to bare aluminum plate and 16.91% higher compared to only black paint coated aluminum plate. On the other hand, the maximum temperature of 74.96°C has been recorded for the identical specimens containing 15 wt% SnO2 under uncontrolled outdoor conditions. The recorded temperature is 47.96% higher than the bare aluminum plate and 14.88% higher than the black paint-coated aluminum plate. The difference of maximum temperatures under indoor and outdoor conditions is due to uncontrolled outdoor conditions and convective losses.